The Effectiveness Of Guided Imagery Relaxation Therapy In Reducing Anxiety Levels In Pre-Operative Patients In The Marwah Inpatient Ward, Bakti Timah Hospital, Pangkalpinang - Ulfah Fitriyatul Mardiyah; M. Jamaluddin (CV. AFDIFAL MAJU BERKAH, 2026)
Anxiety is a psychological response often experienced by patients before undergoing surgery and can affect their physical and psychological readiness. This study aims to determine the effectiveness of guided imagery relaxation therapy in reducing anxiety levels in preoperative patients in the Marwah Inpatient Ward, Bakti Timah Hospital, Pangkalpinang. The study used a descriptive method with a case study approach. The subjects consisted of three preoperative patients experiencing anxiety and were selected based on inclusion criteria. Data collection was carried out using a nursing assessment format, observation sheets, the Hamilton Anxiety Rating Scale (HARS), documentation, and the Standard Operating Procedures for guided imagery therapy. Data analysis was carried out descriptively by comparing the patient's condition before and after the intervention for 3x24 hours. The results showed that all patients experienced a decrease in HARS scores, namely Mrs. A from 24 to 15, Mr. B from 22 to 14, and Mrs. C from 26 to 16. In addition, patients showed a decrease in fear, increased comfort, better sleep quality, and improved vital signs. It was concluded that guided imagery relaxation therapy was effective in helping to reduce anxiety levels and increase patient readiness in facing surgery so that it could be applied as a non-pharmacological nursing intervention in pre-operative patients.